2020
DOI: 10.1111/eea.12991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold stress on metabolic regulation in the overwintering larvae of the Chinese white pine beetle, Dendroctonus armandi

Abstract: The Chinese white pine beetle, Dendroctonus armandi Tsai & Li (Coleoptera: Curculionidae, Scolytinae), is considered the most destructive forest pest in the Qinling and Bashan Mountains of China. In recent years, winter temperature has dropped in these regions, and extremely low temperatures are hard to survive for insects. Cold hardiness becomes a crucial strategy because temperature change often leads to fluctuations in insect abundance, and the metabolism rate is a key index of resistance to cold in overwin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…RNA interference (RNAi) technology has now become a widely used tool to analyze the gene functions of Chinese white pine beetle ( Dendroctonus armandi Tsai and Li). Chen‘s team used RNAi to investigate and analyze the olfactory receptor coreceptor ( DarmOrco ), chemoreceptor ( DarmCSP2 ), aquaporins ( DaAqps ), antifreeze protein genes ( DaAFP ), Capa peptide receptors ( DaCapaRs ), neuropeptide F ( DaNPF ), and 3-hydroxy-3-methylglutaryl coenzyme A reductase genes ( HMGR ) in D. armandi ( Zhang et al, 2016 ; Li et al, 2018 ; Fu et al, 2019 , 2020 , 2021 ; Liu et al, 2021 ; Sun et al, 2021 ). Sun et al (2022) discovered that allatostatin C (PISCF/AST) and juvenile hormone acid O-methyltransferase ( JHAMT ) were major regulators of juvenile hormone synthesis in D. armandi after obtaining dsRNA technology via the L4440 vector construction.…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference (RNAi) technology has now become a widely used tool to analyze the gene functions of Chinese white pine beetle ( Dendroctonus armandi Tsai and Li). Chen‘s team used RNAi to investigate and analyze the olfactory receptor coreceptor ( DarmOrco ), chemoreceptor ( DarmCSP2 ), aquaporins ( DaAqps ), antifreeze protein genes ( DaAFP ), Capa peptide receptors ( DaCapaRs ), neuropeptide F ( DaNPF ), and 3-hydroxy-3-methylglutaryl coenzyme A reductase genes ( HMGR ) in D. armandi ( Zhang et al, 2016 ; Li et al, 2018 ; Fu et al, 2019 , 2020 , 2021 ; Liu et al, 2021 ; Sun et al, 2021 ). Sun et al (2022) discovered that allatostatin C (PISCF/AST) and juvenile hormone acid O-methyltransferase ( JHAMT ) were major regulators of juvenile hormone synthesis in D. armandi after obtaining dsRNA technology via the L4440 vector construction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the protective function of trehalose against potential harm that is induced by cold stress in overwintering insects. A marked increase in trehalose concentration was found in Drosophila immigrans after their recovery from cold stress conditions [ 16 ]. Wharton [ 32 ] has indicated that trehalose acts as a cryoprotectant in alpine weta ( Hemideina maori ) and alpine cockroach ( Celatoblatta quinquemaculata ) when they acclimate to rapid cold hardening.…”
Section: Discussionmentioning
confidence: 99%
“…Low winter temperatures limit the insect populations, activities, and development. The ability to survive annual temperature minima could be a key determinant of insect distribution [ 16 ]. A high level of trehalose in the body plays a key role in protecting them against chilling stresses [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations